Nation, Values and State Traditions in the Masterpiece of World Literature of a Thousand Years (Eurasian Research Bulletin, 2022)
This article discusses the new structure in our society, its formation, and its expression in the work of Yusuf Khos Hajib, "Qutadgu Bilig" ("Knowledge that Leads to Happiness"), a masterpiece of the thousand-year-old world literature. The views expressed in this work teach the values of national statehood that emerged for the first time in the Turkish Islamic region. In it, it is clear that secular statehood has come to the fore.